CORRELATION OF ATHEROGENIC INDEX OF PLASMA WITH STENOSIS LEVEL OF CORONARY ARTERY IN ACUTE CORONARY SYNDROME - Ilhamifithri Ilhamifithri; Rismawati Yaswir; Eugeny Alia; Efrida Efrida (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Atherogenic dyslipidemia is the main risk factor of Acute Coronary Syndrome (ACS), caused atherosclerosis plaque and stenosis of artery coronary. Lipid profile ratio used as a marker of cardiovascular disease severity. Atherogenic Index of Plasma (AIP) calculated as logarithm triglycerides/high-density lipoprotein cholesterol (TG/HDL-C) is a reflection of plasma atherogenicity degree and indicator of small dense low-density lipoprotein (LDL). Small dense LDL is the best predictor for cardiovascular disease, but expensive and difficult to examined. The aim of this study to determine the correlation of AIP with stenosis level of the coronary artery in ACS. This research was an analytical study with cross-sectional design in 24 ACS patients meet the inclusion and exclusion criteria and conduct blood tests at the Central Laboratory Installation of Dr. M. Djamil Hospital Padang in January 2017- September 2017. Triglycerides and HDL-C performed by an enzymatic colorimetric method and stenosis level determined by coronary angiography. Spearman correlation was used to analyze correlation of atherogenic plasma index with stenosis level of the coronary artery, significant if p<0.05. The subjects of this study were 20 males (83.3%) and 4 females (16.6%) with mean age 57.6(7.9) years. The mean level of HDL cholesterol and triglycerides in ACS were 34.8 (8.7) mg/dL and 155.8 (51.8) mg/dL. The mean level of AIP in ACS was 0.28 (0.18). Median of stenosis level of coronary artery was 80% with range 50% - 95%. Spearman correlation test showed a moderate positive correlation between AIP with stenosis level of the coronary artery in ACS (r= 0.426 ; p<0.05). There is a moderate positive correlation between AIP with stenosis level of the coronary artery in ACS.